Continuous Fraud Assessment within the External Auditing (The Journal of Forensic Accounting Profession, 2022)
This paper is dealing with the first pioneering steps to introduce continuous fraud risk assessment tools and techniques in the medium size audit clients in Montenegro. Based on the available experience and audit evidence data gathered in the period 2019 to 2021 statutory audits of medium size enterprise the clients were open and perceptive to adopt simple techniques of the continuous fraud assessment by applying the MS Excel templates. The beforementioned approach is improving the quality of internal control, lowering the levels of asset’s misappropriation, improving the quality of financial and non-financial reporting, regulatory compliance and significantly preventing illegal acts within the enterprise.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2022-0004, pod licencom CC BY-NC-ND 4.0)
Keywords: Continuous auditing; Fraud; Risk Assessment; Montenegro